Accelerated acquisition in pure-shift spectra based on prior knowledge from 1H NMR. Issue 64 (24th July 2019) - Shchukina, Alexandra; Kaźmierczak, Magdalena; Kasprzak, Paweł; Davy, Matthew; Akien, Geoffrey R.; Butts, Craig P.; Kazimierczuk, Krzysztof
Abstract : Pure shift NMR with maximum performance by non-uniform sampling with prior knowledge. Abstract : Pure-shift NMR enhances spectral resolution, but the optimal resolution can only be obtained at the cost of acquisition time. We propose to accelerate pure-shift acquisition using optimised 'burst' non-uniform sampling schemes [I. E. Ndukwe, A. Shchukina, K. Kazimierczuk and C. P. Butts, Chem. Commun., 2016, 52, 12769] and then reconstruct the undersampled signal mathematically. Here, we focus on the reliability of this reconstruction depending on the sampling scheme and present a workflow for the sampling optimization. It is ready to be implemented in routine measurements and yields a great improvement in reconstruction of challenging cases.